Phylogeography of bivalve Meretrix petechialis in the Northwestern Pacific indicated by mitochondrial and nuclear DNA data - Wang, Xiaoxuan (PLoS One, 2017)
The marine clam Meretrix petechialis is an important economic shellfish species in Northwestern Pacific, but little is known about its phylogeographical pattern. Here, we analyzed 311 samples from 22 locations along the northwestern Pacific using combined profiling of one mitochondrial gene (the first subunit of cytochrome coxidase, COI) and one nuclear DNA marker (the internal transcribed spacer region 1, ITS-1) to investigate contemporary genetic structure and reconstruct phylogenetic history of this species. The results revealed that two distinct phylogeographic lineages dominated marginal seas—the East China Sea (ECS) and the South China Sea (SCS) respectively. The estimation of divergence time between two lineages was 2.1–3.8 Ma, corresponding to a period of the early Pleistocene to late Pliocene. The vicariance of the two lineages was connected to the historical isolation of marginal seas and sea surface temperature (SST) gradient, pointing that SST might play an important role in maintaining phylogeographical patterns of M. petachialis. Significant overlaps between two lineages were observed in 23° to 29° N, located at the adjacent area of the ECS and SCS, which might be promoted by the connectivity of China Coast Current. However, the influence of ocean currents on mixings between two lineages was limited. In comparison, significant relationships were found between genetic distances and geographic distances if the North and South populations were analyzed separately, result of which might be due to some small reciprocal, rotating flows along coastal areas and special geographical conditions.